Forces Applied at the Skull Base during Transnasal Endoscopic Transsphenoidal Pituitary Tumor Excision - Bekeny, James R.; Swaney, Philip J.; Webster, Robert J., III; Russell, Paul T.; Weaver, Kyle D. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives Our laboratory is developing a surgical robotic system to further improve dexterity and visualization that will allow for broader application of transnasal skull base surgery. To optimize this system, intraoperative force data are required. Using a modified curette, force data were recorded and analyzed during pituitary tumor excision.Design A neurosurgical curette was modified by the addition of a force sensor. The instrument was validated in an in vitro model to measure forces during simulated pituitary tumor excision. Following this, intraoperative force data from three patients during transnasal endoscopic excision of pituitary tumors was obtained.Setting Academic medical center.Main Outcome Measures Forces applied at the skull base during surgical excision of pituitary tumors.Results Average forces applied during in vitro testing ranged from 0.1 to 0.15 N. Average forces recorded during in vivo testing ranged from 0.1 to 0.5 N. Maximal forces occurred with collisions of the bony sella. The average maximal force was 1.61 N. There were no complications related to the use of the modified curette.Conclusions Forces to remove pituitary tumor are small and are similar between patients. The in vitro model presented here is adequate for further testing of a robotic skull base surgery system.
Keywords: skull base; endoscopic; transnasal; pituitary; Cushing adenoma; surgical robotics; robot; sensor; force